2020
DOI: 10.1101/2020.06.08.20125195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 in first trimester pregnancy – does it affect the fetus?

Abstract: Background Several viral infections are known to be harmful to the fetus in the first trimester of pregnancy and can cause increased nuchal translucency thickness and pregnancy loss. Currently, no evidence exists regarding possible effects of SARS-CoV-2 in first trimester pregnancies. Methods Cohort 1 included pregnant women with a double test taken between Feb. 17 and Apr. 23, 2020, during the SARS-CoV-2 epidemic peak in Denmark. The double test was taken as part of the first trimester risk assessment. Coho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For these reasons, cohort studies were performed on pregnant women infected with SARS-CoV-2 either in their first or second trimester, to seek the correlation between miscarriage and COVID-19. Cosma S et al and La Cour Freiesleben N et al came to the conclusion that there was no correlation between infection in the first trimester and miscarriage referring to their cohort studies [ 51 , 52 , 53 ]. However Shende P et al reported the case of an asymptomatic pregnant woman tested positive for SARS-CoV-2 at her 8th week of gestation who ended up negative at 13th week of gestation with fetal demise revealed by ultrasonography.…”
Section: Immunological Aspects Of Covid-19 In Babiesmentioning
confidence: 99%
“…For these reasons, cohort studies were performed on pregnant women infected with SARS-CoV-2 either in their first or second trimester, to seek the correlation between miscarriage and COVID-19. Cosma S et al and La Cour Freiesleben N et al came to the conclusion that there was no correlation between infection in the first trimester and miscarriage referring to their cohort studies [ 51 , 52 , 53 ]. However Shende P et al reported the case of an asymptomatic pregnant woman tested positive for SARS-CoV-2 at her 8th week of gestation who ended up negative at 13th week of gestation with fetal demise revealed by ultrasonography.…”
Section: Immunological Aspects Of Covid-19 In Babiesmentioning
confidence: 99%
“…In this way, caution is needed when extrapolating this results to the population of other countries. 36 Thus, due to the lack of evidence, it is recommended that embryos/fetuses and or placentae aborted by pregnant women with COVID-19 should be treated as infected tissues and adequately discarded. The study of material via histopathological examination and RT-PCR test for SARS-CoV-2 should be performed whenever it is possible.…”
Section: Abortionmentioning
confidence: 99%
“…We highlight the Danish study that did not find alterations in translucency or double marker test. 36…”
Section: Fetal Malformationmentioning
confidence: 99%
“…Infection was not associated with increased thickness of the nuchal translucency or risk of pregnancy loss. 55 However, other viruses, depending on the gestational age at the moment of infection, have been associated with congenital anomalies and developmental delay later on, like Zika. 56 Thus, the little time since the first studies on the behavior of SARS-CoV-2 is insufficient to evaluate its real impact on neonates.…”
Section: The Health Of the Fetus And The Newbornmentioning
confidence: 99%